Предмет: Алгебра,
автор: Xomiak26
Упростите выражения: (a+3)(a-7)-4a(5-2a)
(a-3)(a-9)-3a(5-2a)
Ответы
Автор ответа:
5
вот правильное решение
Приложения:
![](https://files.topotvet.com/i/412/41267b0ee0c59a13051f1ec0c2ec9931.jpg)
Автор ответа:
2
(a+3)(a-7)-4a(5-2a) = a² -4a -21 -20a +8a² = 9a² -24a -21;
(a-3)(a-9)-3a(5-2a) = a² -12a +27 -15a +6a² = 7a² -27a +27
(a-3)(a-9)-3a(5-2a) = a² -12a +27 -15a +6a² = 7a² -27a +27
Похожие вопросы
Предмет: Геометрия,
автор: antonenkocicka
Предмет: Математика,
автор: comfypavl3437
Предмет: Русский язык,
автор: VIPИмператор
Предмет: Математика,
автор: velogoil444
Предмет: Математика,
автор: lehavargin